Multiple Risk Factors for Work-Related Injuries and Illnesses in Korean-Chinese Migrant Workers. (January 2015) - Lee, Hyeonkyeong; Chae, Duckhee; Yi, Kwan Hyung; Im, Soye; Cho, Sung Hye
Korean-Chinese currently represent the largest group of migrant workers in Korea. The purpose of this study was to investigate the influence of risk factors on the occurrence of work-related injuries and illnesses (WII). Data for 486 Korean-Chinese migrant workers were drawn from the 2010 Migrant Workers' Health and Safety Survey in Korea. Logistic regression was used to identify the association between WII and multiple risk factors. Individual health status (OR = 3.83, 95% CI [2.01, 7.30]), safety training (OR = 0.39, 95% CI [0.18, 0.85]), job satisfaction (OR = 1.90, 95% CI [1.07, 3.38]), physical and chemical hazard exposure (OR = 1.05, 95% CI [1.02, 1.08]), and length of stay (OR = 1.01, 95% CI [1.00, 1.01]) were identified as risk factors for WII. The findings suggest the need for a comprehensive approach to assess WII risk factors, including personal, work organization and psychosocial demands, and acculturation in Korean-Chinese migrant workers.